War and Science in Ukraine - Ina Ganguli; Fabian Waldinger (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
We discuss the impacts of the Russian invasion on Ukrainian science. Using newly collected data, we show that the war has already had significant effects on science in Ukraine: research papers produced by Ukrainian scientists declined by about 10%, approximately 5% of the most prolific scientists are publishing with a foreign affiliation, 22% of top universities have faced destruction of physical capital, and international collaborations with Russian scientists have declined by more than 40%. Drawing upon the economics of science and innovation literature, we highlight three primary channels through which wars impact science: 1) the loss of human capital, 2) the destruction of physical capital, and 3) reductions in international scientific cooperation. The evidence from the literature on the long-run effects of losing human or physical capital indicates that shocks to physical capital can be remedied more easily than shocks to human capital. Our new data also suggests that human capital shocks are the main drivers of the reduction in Ukrainian research output that has occurred since the beginning of the war. Hence, reconstruction efforts should be focused on supporting scientists to continue in the research sector and to return to Ukraine after the war has ended.
Keywords: H52; I23; I25; J44; J61; J62; O38; O52; 330; war and science; scientific human capital; physical capital destruction; international migration; international scientific cooperation